Analisis Hukum Mengenai Kinerja Keuangan Perusahaan dan Pembagian Dividen Terhadap Pemegang Saham di Tinjau dari Current Ratio, Debt to Equinty Ratio dan Turn Over - Sari, Retno Dewi Pulung; Br. Manulu, Golorya (RIO LAW JURNAL, 2024)
This study discusses how the effect of Current Ratio, Debt To Equity Ratio and Turnover on company performance and dividend distribution to shareholders and how the legal impact will be if the company is in bankruptcy. The research method taken by the author is to use the normative juridical method, which discusses research by collecting materials through literature studies. The findings of this study show that share ownership in a company affects how dividends are distributed, as reviewed from the Current Ratio, Debt To Equity Ratio and Turnover where the distribution of shares to shareholders has a positive impact. Article 57 paragraph (1) of the Law contains dividends which are the rights of shareholders. Thus, when the company goes bankrupt, shareholder dividends can also be calculated as a form of company debt. This is possible because the definition of debt in PKPU and the Bankruptcy Law follows the definition of debt in the Civil Code, namely debt in a broad sense with additional discussion about the consequences of corporate bankruptcy.